If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 4(X + -8) + 16 Reorder the terms: 12 = 4(-8 + X) + 16 12 = (-8 * 4 + X * 4) + 16 12 = (-32 + 4X) + 16 Reorder the terms: 12 = -32 + 16 + 4X Combine like terms: -32 + 16 = -16 12 = -16 + 4X Solving 12 = -16 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. 12 + -4X = -16 + 4X + -4X Combine like terms: 4X + -4X = 0 12 + -4X = -16 + 0 12 + -4X = -16 Add '-12' to each side of the equation. 12 + -12 + -4X = -16 + -12 Combine like terms: 12 + -12 = 0 0 + -4X = -16 + -12 -4X = -16 + -12 Combine like terms: -16 + -12 = -28 -4X = -28 Divide each side by '-4'. X = 7 Simplifying X = 7
| 6(x-4)-5(x-2)-7(2x+5)=3 | | 4x^2-20+6x=0 | | 7x-28-3=46 | | 2x+8x+2y^2=0 | | 3x=4-(-14) | | -12+6x-4x=18 | | x^2+y^2+2x+4y-20=0 | | 105x+15x-225=25 | | -4(6m+1)=-17m-18 | | 10x-5(2x+4)=20 | | 7(8v+1)=231 | | 4a-3b=10 | | 10x-x-134=118 | | 1.5x+3x-4=10 | | 15p+7p= | | 2x^2-5x-133=0 | | S=D+pm | | 3*3/10+4=-3 | | -2W+5-3W-4=-9 | | 3*-7/4+4=-3 | | 2.4(2x-2)+2.2x= | | .06x+.5=.123 | | X+45=600 | | (11b-6)-5(2b+4)=-6 | | 10(x+5)=12(x-4) | | 17p+14+19=3 | | x=2*tanh(x) | | 14m=400.0 | | 10x+12=32 | | x=tanh(x) | | x-4.2=6 | | 12.67(a-3)=.5 |